P179 Suprasegmental effects of dorsal transcutaneous spinal Direct Current Stimulation (tsDCS) on the Ia-motoneuron connections. Issue 3 (March 2017) - Cortese, F.; Vergari, M.; Ferrucci, R.; Nigro, M.; Ruggiero, F.; Cogiamanian, F.; Ardolino, G.; Bocci, T.; Barbieri, S.; Priori, A.
Abstract : Introduction: tsDCS is a novel non-invasive tool to modulate human spinal cord function (Cogiamanian et al., 2008). Anodal tsDCS is known to reduce the post activaction depression of the H reflex in the lower limb (Winkler et al., 2010), and to induce a leftward shift of the stimulus–response curve of the H reflex, with no effect on H max/M max ratio (Lamy et al., 2012). No data are available about the effects of tsDCS on the upper limb H reflex. Objectives: To assess whether dorsal tsDCS modulates the cervical Ia-motoneuron connections, we tested the influence of tsDCS on the H reflex in the human upper limb. Materials and methods: tsDCS (2 mA, 20 min) was delivered in 12 healthy volunteers (aged 22–50 yrs, 4 males) through a pair of surface electrodes placed over the spinous processes of T10-12 and above the right shoulder. The H reflex was elicited stimulating the median nerve at the elbow and recording the response with surface electrodes placed over the flexor carpi radialis muscle. Each subject underwent anodal and cathodal tsDCS in random order. H reflex was recorded (i) before tsDCS (T0); (ii) 5 (T1), 10 (T2), 15 (T3) minutes after tsDCS onset; (iii) immediately after tsDCS offset (T4). The H reflex size is expressed as percentage of baseline amplitude (=100%). Values are mean ± SE. Results: The two way ANOVA disclosed a significant "time" × "stimulation" interaction on the percentage change of H reflex amplitude. Post-hoc analysis revealed that anodal tsDCS significantly reduced the H reflex amplitude at T3 (78.3 ± 8.2%; p  = 0, 040) and at T4 (76.3  ± 7.6%; p  = 0.028), whereas cathodal tsDCS significantly increased the H reflex amplitude only at T1 (125.5 ± 11.0%; p  = 0.018). Conclusion: Dorsal tsDCS influences human cervical mono/oligosynaptic Ia-motoneuronal reflex in a polarity specific manner. Because the temporal dynamic of tsDCS-elicited H reflex changes differed between the two polarities, anodal and cathodal tsDCS might have different –not simply specular– mechanisms of action.